(untitled) (Iranian Journal of Kidney Diseases, 2013)
Introduction. Diabetic nephropathy is the major cause of end-stage renal disease worldwide. Silymarin is a flavonoid mixture obtained from Silybum marianum. Various preclinical and clinical studies have revealed that it has antidiabetic activity. The objective of this study was to evaluate the effect of silymarin on type 2 diabetic nephropathy in rats. Materials and Methods. Non-insulin-dependent diabetes mellitus was induced in overnight-fasted male albino Wistar rats by an intramuscular injection of streptozotocin and nicotinamide. Eighteen rats with diabetic nephropathy and 6 rats without induced nephropathy were divided into 4 groups, each containing 6 animals. Group 1 was the normal control and group 2 was the DM control. Groups 3 and 4 were rats with diabetic nephropathy that received 60 mg/kg and 120 mg/kg of silymarin for 60 days. Results. At the end of the study period, the diabetic control group had significantly higher blood glucose, glycosylated hemoglobin, urine volume, serum uric acid, and urine albumin levels when compared to the normal control group. Silymarin-treated groups showed significantly lower levels of blood glucose, glycosylated hemoglobin, urine volume, serum creatinine, serum uric acid, and urine albumin, when compared to the diabetic control group. Histopathological studies reports strongly supported the protective effect of silymarin. Conclusions. These findings suggest that silymarin has protective effects for kidneys affected by type 2 diabetes mellitus. If the safety and efficacy is confirmed in humans, silymarin will be a good medication to prevent nephropathy-induced premature death in diabetic patients.